O lugar da ciência na classificação dos documentos do Archivo Público do Império (1838-1889) - Neves, Joana Asseff (2017)
The present dissertation aims to verify the place of science in the classification of the documentation stored in the Public Archive of the Empire of Brazil. The period from 1838 to 1889 was established from the time of its founding until the time of the Republic. From the relevant legislation (laws, decrees, regulations, etc.) and the reports of the Ministry of the Empire, a historical survey was carried out of the Archivo, highlighting the main events of the period. Thus, to understand the classification of documentation, we analyzed the regulations of 1838, 1860 and 1876, pointing out the incidence of terms related to science; we tried to identify documents related to science deposited in the Archive and its classification; and compared with other classifications that somehow were in dialogue with the one held at the institution. In this way, we believe can understand the place of science in the classification of documents stored in the Archive during the Empire of Brazil